2u+17=-5(u-9)

Simple and best practice solution for 2u+17=-5(u-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2u+17=-5(u-9) equation:


Simplifying
2u + 17 = -5(u + -9)

Reorder the terms:
17 + 2u = -5(u + -9)

Reorder the terms:
17 + 2u = -5(-9 + u)
17 + 2u = (-9 * -5 + u * -5)
17 + 2u = (45 + -5u)

Solving
17 + 2u = 45 + -5u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '5u' to each side of the equation.
17 + 2u + 5u = 45 + -5u + 5u

Combine like terms: 2u + 5u = 7u
17 + 7u = 45 + -5u + 5u

Combine like terms: -5u + 5u = 0
17 + 7u = 45 + 0
17 + 7u = 45

Add '-17' to each side of the equation.
17 + -17 + 7u = 45 + -17

Combine like terms: 17 + -17 = 0
0 + 7u = 45 + -17
7u = 45 + -17

Combine like terms: 45 + -17 = 28
7u = 28

Divide each side by '7'.
u = 4

Simplifying
u = 4

See similar equations:

| -4(u+1)=5u+5 | | X^2dy+y^2dx= | | (2x+4)+(4x+2)=(6x+6) | | 17=3u+2 | | -3x+92=4x+1 | | -11=-8+r-3 | | -12=5x+8x | | 6(-1-7k)=-8(7-k) | | 8(9-2k)=9(1-k) | | 8x+38=6x+6240 | | -11(8m-6)=-2-7(12m-8) | | -23+6x=5x+2(5x+2) | | 8p+21=-3(-8p-7) | | -11=8+r-3 | | (12x-8)+(12x-8)=(22x-11) | | 2(5+5k)=4+8k | | 1d/10-12 | | 3-1/t-2/t^2=0 | | lx-2l=2x+1 | | f(x)=7x^2+4x-3 | | 0.05x-0.1x+0.6=0.04x+2.22 | | (8x-3)+(8x-3)=(10x+30) | | =29*4 | | 7700+1900+700+160= | | 0.05x-0.1x+0.6=0.04+2.22 | | 0.05-0.1x+0.6=0.04+2.22 | | =(81+162t^2+81t^4) | | =sqrt(81+162t^2+81t^4) | | 4.25E-19= | | =32sin^2(t)cos^2(t) | | F=7/4(n-9) | | 1/2*3x*4x=216 |

Equations solver categories